Sensitivity analysis with MC simulation for the failure rate evaluation and reliability assessment. (October 2015) - Catelani, M.; Ciani, L.; Venzi, M.
Highlights: Sensitivity analysis is carried out to assess propagation of uncertainty. The proposed approach is based on Monte Carlo simulation. Failure rate evaluation and reliability assessment is discussed. Abstract: The paper focuses on sensitivity analysis achieved on a mathematical model for system reliability assessment: the aim of this study is to assess propagation and quantification of uncertainty from input (e.g. nominal values of failure rates taken from a generic database) to output (e.g. system reliability). Many sources of uncertainty affect input data so a limit in the confidence on the response of the model is considered. After the definition of the variability range of possible input and its associated distribution, Monte Carlo simulation is used to have a wide sample of survey. In this paper sensitivity analysis is achieved on reliability outcomes of a generic SIS ( Safety Instrumented System ) constituted by sensors, logic solver and final elements; SIS is used to implement one or more safety functions to control critical processes on plants in order to avoid unacceptable or dangerous conditions. The results obtained with MC simulation and the following sensitivity analysis prove the validity of the proposed approach.